An immunogenetic heterogeneity in multiple sclerosis. Issue 10 (October 1992) - Hillert, J; Grönning, M; Nyland, H; Link, H; Olerup, O
Abstract : Two clinical forms of multiple sclerosis (MS), primarily chronic progressive MS (PCP MS) and relapsing/remitting MS (R/R MS) have been shown to differ in several respects. The results of genomic HLA class II typing with restriction fragment length polymorphism analysis of 62 MS patients from Western Norway, 42 with R/R MS and 20 PCP MS, are reported on here. As in previous studies of Swedish patients, the haplotype DRw17(3), DQw2 was found to be five times more common in R/R MS than in PCP MS. This finding supports the hypothesis that R/R and PCP MS are immunogenetically separate entities. In contrast with a previous investigation of Norwegian MS patients, no association of MS with glutamine at position 34 of the HLA-DQ alpha chain or with defined sequences of the HLA-DQB1 gene was found.